Delivering on the WTO Round : a high-level government-business dialogue - United Nations. Economic and Social Commission for Asia and the Pacific; Conference on Delivering on the WTO Round: A High-Level Government-Business Dialogue for Development (2005 : Macao, China) (New York : United Nations, 2005)
The articles in this publication provide insights into the status of the negotiations in the main areas of the Doha Development Agenda and interlinkages between trade liberalization in those areas to business and economic development in Asia and the Pacific. It contains both qualitative and quantitative assessments of trade liberalization at multilateral regional/bilateral levels for poverty reduction and development. Special attention is given to harnessing the trade negotiation process to the realization of the Millennium Development Goals.--Publisher's description
Global trade liberalization and poor countries : poverty impacts and policy implications -- The Doha development agenda and an enhanced global partnership for development : promise or reality? -- Multilateralizing regionalism : towards an integrated and outward-oriented Asia-Pacific economic area -- Liberalization in agricultural trade : issues and concerns -- Services : importance of further liberalization for business and economic development in the region -- Trade facilitation : issues and negotiations -- Trade adjustment and business development financing
"Papers and statements presented at the Conference on Delivering on the WTO Round: A High-level Government-Business Dialogue for Development, organized in collaboration with the International Trade Centre UNCTAD/WTO and Government of Macao, China ; Macao, China, 4-6 October 2005."
"Sales No. E.06. II. F.4"--Title page verso
"ST/ESCAP/2393"--Title page verso
At foot of title: Economic and Social Commission for Asia and the Pacific
Includes bibliographical references
1
Keywords: Industrial policy -- Congresses; International trade -- Congresses; Industrial policy; International trade; Conference papers and proceedings